Evaluation of environmental and local factors on urban sarcosaprophagous Diptera: a case study with Sarcophagidae. Issue 2 (28th September 2020) - Battán‐Horenstein, M.; Mulieri, P. R.; Gleiser, R. M.
Abstract: The urbanization process affects the structure of insect communities, favouring biotic homogenization processes by promoting adequate conditions for the establishment of synanthropic species. Considering the scarce knowledge about the ecology of Neotropical sarcophagids, we compared the flesh fly community from two different urban zones in two contrasting seasons and examined the response of the Sarcophagidae assemblage to landscape and microhabitat variables. Adult flies were collected in 13 sites with two traps (total number of traps 26) baited with 200 g of hydrated bone meal. A total of 2312 adult sarcophagids were collected belonging to 27 species; Oxysarcodexia paulistanensis (Mattos, 1919) represented >48% of the total sample. The local factor of insolation explained both the abundance and species richness of sarcophagids, collections being higher and richer in traps exposed to sunlight compared with traps placed in the shade regardless of the season. Richness was also affected by the environment, being higher in traps exposed in suburban rather than urban sites. The combination of these factors (sub‐urban environment and availability of open areas) could explain the Sarcophagidae assemblage. The average number of sarcophagid species collected was related to the season, providing a good opportunity to assess the temporal variability of this family in the region. Abstract : The urbanization process affects the structure of insect communities, favouring biotic homogenization processes by promoting adequate conditions for the establishment of synanthropic species. Considering the scarce knowledge about the ecology of neotropical sarcophagids, the flesh fly community from two different urban zones, in two contrasting seasons was compared and examined the response of the Sarcophagidae assemblage to landscape and microhabitat variables. The combination of environmental (non‐urban environment) and local factors (availability of open and clearer areas) explained the Sarcophagidae assemblage.